Association between serum transaminase levels and insulin resistance in euthyroid and non-diabetic adults: Serum transaminase levels and insulin resistance in healthy adults - Yamamoto, Jin Marcos (2020)
Aim: To evaluate the association between elevated serum transaminase levels and insulin resistance (IR) in a population of healthy individuals. Methods: We define IR with a cut-off point of homeostatic model assessment (HOMA-IR) ≥ 3.8. For aspartate aminotransferase (AST), we consider elevated values >30 U/L in women and values >36 U/L in men. For alanine aminotransferase (ALT), we consider elevated values >30 U/L in women and values >40 U/L in men. We performed a crude and adjusted generalized linear model from Poisson family with robust variance, in order to evaluate the association between elevated serum transaminase levels and IR. The associations were presented as prevalence ratio (PR) with their respective 95% confidence intervals (95% CI). Results: We included 261 participants in the study. The median age was 39 years (31–45) and 23.7% of the participants were men. The prevalence of elevated serum transaminase for AST and ALT were, 13.8% and 26.1%, respectively. The prevalence of IR was 34.1%. In the crude analysis we found statistical significance between elevated AST and ALT with IR (PR = 3.18; 95% CI: 2.33–4.34 and PR = 2.44; 95% CI: 1.88–3.30; respectively). However, in the multivariate analysis, the association only remained statistically significance with ALT, but lost its significance with AST, PR = 1.90; CI 95%: 1.31–2.77 and a PR = 1.23; CI 95%: 0.93–1.61; respectively. Conclusion: Elevated serum levels of ALT were associated with insulin resistance. ALT could be used in clinical practice as an additional tool to assess IR in apparently healthy people.